Effects of an azasterol inhibitor of sterol 24-transmethylation on sterol biosynthesis and growth of Leishmania donovani promastigotes. - Haughan, P A (1995)
Leishmania donovani promastigotes were cultured in the presence of an azasterol (20-piperidin-2-yl-5 alpha-pregnane-3 beta,20-diol) to determine the effects on sterol biosynthesis and cell proliferation. Inhibition of growth increased gradually with azasterol concentrations up to 5 micrograms/ml; concentrations of azasterol exceeding 5 micrograms/ml were lethal. Sterol biosynthesis was affected by the azasterol when administered at concentrations as low as 100 pg/ml. The primary site of action was the alkylation at C-24 of a delta 24-sterol precursor. The 24-alkylated sterols [ergosta-5,7,24(24(1))-trien-3 beta-ol and ergosta-5,7,22-trien-3 beta-ol] of the protozoan were replaced by delta 24-cholesta-type sterols which then accumulated in the cells. Administration of the azasterol together with a bis-triazole inhibitor of the 14 alpha-methylsterol 14-demethylase reaction, which operates in sterol biosynthesis, resulted in depletion of 24-alkylsterols and their replacement with predominantly 14 alpha-methylsterols lacking a 24-alkyl group. Continuous subculture of promastigotes in the presence of the azasterol resulted in gradual depletion of 24-alkylsterols and their complete replacement by delta 24-cholesta-type sterols. Transfer of the azasterol-treated cells to medium lacking azasterol resulted in a gradual restoration, after several subcultures, of the normal 24-alkylsterol pattern. The results indicate that, although 24-alkylsterols are normally produced by the protozoan, it can nevertheless survive with sterols possessing only the cholestane skeleton. Thus there is no absolute requirement for 24-alkylsterols to fulfil some essential 'sparking' role associated with cell growth in promastigotes.